Deciphering the impact of TERT/telomerase on immunosenescence and T cell revitalization - Huang, Lingyi; Zhang, Mingfu; Bai, Ding; Qu, Yi (Frontiers in Immunology, 2024)
Immunosenescence impacts both the innate and adaptive immune systems, predominantly affecting certain immune cell types. A notable manifestation of immunosenescence is the diminished efficacy of adaptive immunity. The excessive senescence of immune cells, particularly T cells, leads to marked immune deficiency, consequently escalating the risk of infections, tumors, and age-associated disorders.Lymphocytes, especially T cells, are subject to both replicative and premature senescence.Telomerase reverse transcriptase (TERT) and telomerase have multifaceted roles in regulating cellular behavior, possessing the ability to counteract both replicative and premature senescence in lymphocytes. This review encapsulates recent advancements in understanding immunosenescence, with a focus on T cell senescence, and the regulatory mechanisms involving TERT/telomerase. Additionally, it comprehensively discusses strategies aimed at inhibiting immunosenescence by augmenting TERT/telomerase activity.